Pengaruh Perilaku Belajar Ditinjau dari Gaya Belajar Siswa Terhadap Hasil Belajar Siswa - Aluh Adinda Maharani Putri; Sridana, Nyoman; Novitasari, Dwi (FKIP Universitas Mataram, 2025)
This study aims to determine the influence of learning behavior in terms of students' learning styles on the mathematics learning outcomes of eighth-grade students at SMPN 10 Mataram in the 2024/2025 academic year. This research uses a quantitative approach with the Ex Post Facto research method. The population of the study consists of all eighth-grade students at SMPN 10 Mataram in the 2024/2025 academic year, totaling 271 students across 9 classes. The sample used is class VIII E, consisting of 32 students selected using cluster random sampling. Data collection techniques involved questionnaires and tests. The instruments used include a learning style questionnaire, a learning behavior questionnaire, and a mathematics learning outcomes test. The learning outcomes test administered was a post-test on the topic of Systems of Linear Equations in Two Variables (SPLDV). The instruments were validated using Aiken’s V index, which showed validity with V values of 0.972 for the learning style and learning behavior questionnaires, and 0.946 for the learning outcomes test. Data analysis techniques used in this study included descriptive and inferential statistical analysis. The results of the study indicate that there is a positive and significant influence of learning behavior on learning outcomes, with a contribution of 26.7%, and a positive and significant influence of learning behavior in students with a kinesthetic learning style on learning outcomes, with a contribution of 40.9%. Thus, it can be concluded that learning behavior in terms of students' learning styles has an influence on mathematics learning outcomes of eighth-grade students at SMPN 10 Mataram.